Strategi Sekolah Dalam Meningkatkan Jumlah Peserta Didik Di Madrasah Ibtidaiyah Mathlaul Anwar Bogor - Usup Usup; Dewi Utami; Dadan Mardani (Pusat Riset dan Inovasi Nasional, 2023)
The world of education today must be treated and managed professionally, because of the increasingly fierce competition. Madrasah with good assessment in the eyes of the community will have a good impact on the madrasa. This requires a strategy carried out by the Head of madrasah so that the madrasah he leads becomes a favorite. The purpose of this study is to explain the strategies used and the constraints faced in the strategy of Madrasah Ibtidaiyah Mathlaul Anwar Tegal Waru Ciampea Bogor to increase the number of students. This research is a research using qualitative methods. This qualitative research method was chosen because the researcher intends to describe and analyze certain phenomena in depth and detail. Data collection methods used by observation, interviews and documentation. The results of research on the strategy carried out by MI Mathlaul Anwar Ciampea Bogor by applying two strategies. First, the intern strategy with two steps, 1) Improving the quality of students, 2) Improving infrastructure. Second, the external strategy is, 1) Brochure distribution, 2 Openings for Marawis and Tahfiz extracurricular activities. The obstacles faced by madrasah are; 1) the location of the madrasa is far from the city center 2) There is intense competition between educational institutions, 3) The Covid-19 pandemic situation forces online learning.